2018
DOI: 10.1111/jne.12537
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous neurosteroids influence synaptic GABAA receptors during postnatal development

Abstract: GABA plays a key role in both embryonic and neonatal brain development. For example, during early neonatal nervous system maturation, synaptic transmission, mediated by GABA A receptors (GABA A Rs), undergoes a temporally specific form of synaptic plasticity to accommodate the changing requirements of maturing neural networks. Specifically, the duration of miniature inhibitory postsynaptic currents (mIPSCs), resulting from vesicular GABA activating synaptic GABA A Rs, is reduced, permitting neurones to appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 147 publications
(355 reference statements)
0
12
0
Order By: Relevance
“…Steroidogenesis also occurs in the placenta, and in both sexes, the adrenal cortex and brain. Many locally derived "neurosteroids" influence brain development and function (Belelli et al, 2018;Do Rego et al, 2009;London, 2016). Classic experiments have demonstrated that manipulation of hormone levels can profoundly alter sex-typical reproductive and BOX 1 TOOLS FOR STUDYING GENE REGULATORY MECHANISMS IN SPECIFIC CELL TYPES OF THE MOUSE BRAIN Several molecular genetic tools have been developed for studying gene regulation in the mammalian brain.…”
Section: Gonadal Steroid Hormones Direct Sexual Differentiation Of mentioning
confidence: 99%
“…Steroidogenesis also occurs in the placenta, and in both sexes, the adrenal cortex and brain. Many locally derived "neurosteroids" influence brain development and function (Belelli et al, 2018;Do Rego et al, 2009;London, 2016). Classic experiments have demonstrated that manipulation of hormone levels can profoundly alter sex-typical reproductive and BOX 1 TOOLS FOR STUDYING GENE REGULATORY MECHANISMS IN SPECIFIC CELL TYPES OF THE MOUSE BRAIN Several molecular genetic tools have been developed for studying gene regulation in the mammalian brain.…”
Section: Gonadal Steroid Hormones Direct Sexual Differentiation Of mentioning
confidence: 99%
“…It was named a neurosteroid in 1981 by Baulieu's team, who discovered that the brain "acting like a peripheral gland" expresses the enzymatic machinery required to synthesise allopregnanolone de novo starting from pregnenolone, the precursor of all neurosteroids (Corpéchot et al 1981). Allopregnanolone's anti-convulsant, anxiolytic and anti-depressant pharmacological effects after its administration in animals and humans were soon recognised to be mediated by a mechanism of action that includes the fast allosteric modulation of the action of GABA at GABA A receptors (Majewska et al 1986;Belelli et al 2018). The neurophysiological role of allopregnanolone in permitting the finetuning and regulation of the strength of GABA A receptors to agonists, positive allosteric modulators, and GABAmimetic agents, was also unveiled (Pinna et al 2000).…”
Section: название разделаmentioning
confidence: 99%
“…Importantly, the affinity and relative potency of 3α-hydroxy, 5α-reduced for the GABA A receptor is highly dependent on the subunit composition of the receptor itself. The GABA A receptor is a pentamer that is typically composed of two α subunits (α1–6), two β subunits (β1–4), and one additional subunit that is either a γ (γ1–3), δ, ε, π, or θ, or ρ (ρ1–3; Sieghart, 2006 ; Reddy and Jian, 2010 ; Belelli et al, 2018 ). A low-affinity human β3 homopentamer of the GABA A has been identified as well (Miller and Aricescu, 2014 ), though this conformation of the receptor does not appear to be neurosteroid-sensitive, probably due to the lack of α subunits (Nik et al, 2017 ).…”
Section: α-Hydroxy 5α-reduced Neurosteroids As Regulators Of Gaba mentioning
confidence: 99%